2021
DOI: 10.3390/jcm10173973
|View full text |Cite
|
Sign up to set email alerts
|

Myeloma Bone Disease: The Osteoblast in the Spotlight

Abstract: Lytic bone disease remains a life-altering complication of multiple myeloma, with up to 90% of sufferers experiencing skeletal events at some point in their cancer journey. This tumour-induced bone disease is driven by an upregulation of bone resorption (via increased osteoclast (OC) activity) and a downregulation of bone formation (via reduced osteoblast (OB) activity), leading to phenotypic osteolysis. Treatments are limited, and currently exclusively target OCs. Despite existing bone targeting therapies, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 111 publications
(134 reference statements)
1
11
0
Order By: Relevance
“…It has been shown that CD38 is expressed by effectors and inhibitory cells and by osteoblasts. CD38 also appears to be involved in the formation and differentiation of osteoclasts and may play a role in bone remodeling [ 86 , 87 ]. Hence, there is a rationale for using the anti-CD38 monoclonal antibody (Daratumumab) against MM bone disease and the protection of MM PCs by BMSCs [ 86 , 87 , 88 ].…”
Section: Cytokines and Bone Resorptionmentioning
confidence: 99%
“…It has been shown that CD38 is expressed by effectors and inhibitory cells and by osteoblasts. CD38 also appears to be involved in the formation and differentiation of osteoclasts and may play a role in bone remodeling [ 86 , 87 ]. Hence, there is a rationale for using the anti-CD38 monoclonal antibody (Daratumumab) against MM bone disease and the protection of MM PCs by BMSCs [ 86 , 87 , 88 ].…”
Section: Cytokines and Bone Resorptionmentioning
confidence: 99%
“…In the study by Wang et al (2014), gambogic acid treatment suppressed MM progression and angiogenesis through inhibition of HIF1α/VEGF expression, which was associated with the inhibition of PI3K/Akt/ mTOR pathway. Osteoporosis and lytic lesions are also common in patients with MM (Andrews et al, 2021). Stromal cell-derived factor 1α (SDF-1α)/CXC chemokine receptor 4 (CXCR4) signaling has been shown to be associated with osteoclastogenesis (Dong et al, 2016).…”
Section: Gambogic Acidmentioning
confidence: 99%
“…Simultaneously, myeloma cells inhibit osteoblast formation, thereby preventing formation of new bone and exacerbating the impact of the osteolytic bone disease. The vicious cycle and the many factors that stimulate osteoclasts and inhibit osteoblasts have been described previously in a number of reviews (26)(27)(28)(29).…”
Section: Myeloma Pathogenesis and Bone Diseasementioning
confidence: 99%
“…The pathogenesis of myeloma is facilitated by the direct and indirect interactions between myeloma cells and microenvironment cells ( 26 29 ). Of particular relevance to the development of myeloma bone disease and control of myeloma dormancy are osteoclasts, osteoblasts and bone lining cells ( 19 , 26 , 29 31 ).…”
Section: Myeloma Pathogenesis and Bone Diseasementioning
confidence: 99%
See 1 more Smart Citation